2018
DOI: 10.1038/s41388-018-0175-6
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β promotes renal cell carcinoma progression via regulating LncRNA HOTAIR-miR-138/200c/204/217 associated CeRNA network

Abstract: Recent studies indicated that the estrogen receptor beta (ERβ) could affect the progression of prostate and bladder tumors, however, its roles in the renal cell carcinoma (RCC), remain to be elucidated. Here, we provide clinical evidence that ERβ expression is correlated in a negative manner with the overall survival/disease-free survival in RCC patients. Mechanism dissection revealed that targeting ERβ with ERβ-shRNA and stimulating the transactivation of ERβ with 17β-estradiol or environmental endocrine disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 49 publications
2
87
1
Order By: Relevance
“…The elevated expression of Hotair was observed in multiple cancer types, [16][17][18] and our results also demonstrated that it was significantly upregulated in a panel of CRC cells ( Figure 1A). In 20 paired CRC clinical specimens, the expression of Hotair was increased in CRC tissues when compared with their adjacent nontumor tissues ( Figure 1B).…”
Section: Hotair Was Significantly Upregulated In Crc Cells and Clinsupporting
confidence: 75%
“…The elevated expression of Hotair was observed in multiple cancer types, [16][17][18] and our results also demonstrated that it was significantly upregulated in a panel of CRC cells ( Figure 1A). In 20 paired CRC clinical specimens, the expression of Hotair was increased in CRC tissues when compared with their adjacent nontumor tissues ( Figure 1B).…”
Section: Hotair Was Significantly Upregulated In Crc Cells and Clinsupporting
confidence: 75%
“…Antagonizing behaviour of this lincRNA sponge the activity of miR-138/204/217 complex, among which miR-138/217 negatively regulate EZH2. This leads to upregulation of EZH2 and epigenetically promoter silencing of miR-200c downstream of HOTAIR, consequently directing malignant cells to proliferation and invasion [84]. Interestingly, ERβ could play crucial role in breast cancer cells progression, particularly EMT and metastasis [85].…”
Section: Hotair and Oncogenesmentioning
confidence: 99%
“…LncRNAs is well-known as endogenous competitively RNAs (ceRNA) in human cancers, thereby modulating their downstream gene expression. [16][17][18][19] Here, we explored whether ARAP1-AS1 can act as a ceRNA to regulate cellular processes in BCa. Mechanism experiments were designed and applied to detect the ceRNA pathway which centered with lncRNA ARAP1-AS1.…”
Section: Introductionmentioning
confidence: 99%